Can Survey Participation Alter Household Saving Behavior? - Joachim Winter; Thomas Crossley; Jochem de Bresser; Liam Delaney (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Much empirical research in economics is based on data from household surveys. Panel surveys are particularly valuable for understanding dynamics and heterogeneity. A possible concern with panel surveys is that survey participation itself may alter subsequent behavior. We provide novel evidence of survey effects on household financial behavior in a developed country. We exploit randomized assignment to survey modules within the LISS-panel, an internet panel survey which is representative of the Dutch population. Our saving measure is based on linked administrative wealth data, allowing us to distinguish changes in saving behavior from changes in reporting behavior. We find that households that respond to detailed questions on expenditures and needs in retirement reduced their non-housing saving rate by 3 percentage points. The size of the effect is increasing in the education level of the household. One interpretation is that the survey acted as a salience shock.
Keywords: C83; C81; D14; 330